Identifikasi Kualitatif Tingkat Kompetisi Bisnis Fotografi dan Alternatif Tindakan untuk Menghadapainya - M. Kholid Arif Rozaq (Rekam: Jurnal Fotografi, Televisi, Animasi)
Photo studio is an exciting venture and a growing number who started it. This effort is essentially a business-related field of recording media. These businesses receive services in the field of Photography and Video Recording, it becomes a necessity in documenting the important moments in human life. Regarding of photo studio, one thing that is interesting to examine is the level of competition among business photography. The study tries to offer a concept of Porter's five forces analysis.This study is a descriptive research and qualitative analysis. According to Robert K. Yin (2011), one of the methods that can be used in qualitative research is to conduct indepth interviews (depth interviews) on the object of research.Some of the dominant characteristics of the most prominent are (1) market size, (2) the pace of technological change and innovation, (3) capital requirements and the ease of entry and exit of business, (4) Scope of Competitive rivalry, (5) industry Profitibility and (6) the degree of product differentiation.Verification has been done to conclude that the level of competition in the photography business is high. The implication is that the structure of the industry is "less profitable" for participating companies to gain profit. Therefore, it is necessary to make strategic steps to win the competition. The steps are basically to reduce the level of competition that occurs.